Parent-Student Partnership and School in Improving Student Achievement at SDN Dawuhan 03, Sirampog District - Supriyanto , Wandi; Oktarina, Nina (Universitas Negeri Semarang, 2025)
Partnerships between parents and schools play an important role in improving student achievement, especially at the primary school level. This study aims to analyze the forms of partnership, the level of parental involvement and its impact on student achievement at SDN Dawuhan 03, Sirampog sub-district. Using a qualitative case study approach, data was collected through interviews, observation and documentation. The results show that the forms of partnership include six types of involvement according to Epstein, namely parenting, communication, volunteering, learning at home, decision-making, and collaboration with the community. The level of parental involvement is generally still in the instrumental and representative categories according to Sarah C. White's typology. Nevertheless, this involvement has a positive impact on students' academic and non-academic achievements. This study recommends the need to strengthen partnership programs based on two-way communication and more participatory parenting training to increase parental involvement in a transformative and sustainable manner.